Layanan Bimbingan Dan Konseling Terhadap Anak Terlantar Di Rehabilitasi Sosial UPTD PSBS Dinas Sosial Provinsi Kepulauan Bangka Belitung - Nurviyanti Cholid; Yulinda Yulinda (Counselle| Journal of Islamic Guidance and Counseling, 2021)
Abstract Guidance and Counseling Services for Abandoned Children and Abandoned Persons/Elderly in Social Rehabilitation UPTD PSBS Social Service of the Archipelago Province. This research is a descriptive qualitative research that aims to find out how the guidance and counseling services provided to neglected children and the elderly in social rehabilitation UPTD PSBS Social Service of the Bangka Belitung Islands Province. The data sources used are primary data, namely the Head of the Social Apocation Program, the Head of Subdivision of TU, ​​and the Head of Guidance and the secondary data are books, journals, theses, archives, and official documents at the Office of Social Institutions for Bina Serumpun Province of the Bangka Belitung Islands Province. Collecting data using the method of observation, interviews and documentation. The results showed that: Guidance and counseling services for abandoned children and abandoned people in the UPTD PSBS of the Archipelago Province Social Service can be classified into eight stages, namely the first stage: Initial Approach, second stage: acceptance, third stage: care, fourth stage: maintenance, and Social Protection Care, Fifth Stage: Assessment Stage, Sixth Stage: Coaching Stage, Seventh Stage: Distribution Stage, Eighth Stage: Termination Stage.